Evolution of Self-Repair Behaviour in Narration Among Adult Learners of French as a Second Language - Simard, Daphnée; French, Leif; Zuniga, Michael (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2017)
Self-repairs, or revisions of speech that speakers themselves initiate and complete (Salonen & Laakso, 2009), have long been associated with second language (L2) development (e.g., Kormos, 2000a). To our knowledge, however, no research has looked at the evolution of self-repair correctness patterns, that is, the correctness of elements targeted for repair and the correctness of the repair outcomes. Consequently, the present study sought to investigate changes in the self-repair behaviour of English-speaking L2 learners of French over the course of a 5-week period and to verify whether any changes occurred over time. Speech samples of the L2 were collected from 50 adult participants through an elicited narration task at the beginning (Time 1) and the end (Time 2) of a 5-week immersion program. Overall, the results showed that there were qualitative and quantitative changes in self-repairs types, and that correctness of the element being repaired increased significantly over time.